The design and techno economic analysis of a succinic acid production facility - Tomczyk, Sarah; Ozturk, Serdar; Wawrzyniak, Thomas; Tessman, Monica; Ehrlich, Christopher; Shaikh, Faisal (Frontiers in Sustainability, 2022)
Succinic acid is an industrially important commodity chemical that acts as a precursor to numerous other chemicals. This article explores an alternative biochemical route (as opposed to the traditional route from petroleum), by modeling a succinic acid production plant using Actinobacillus succinogenes, to convert the renewable sugars of corn stover feedstock. The model developed with SuperPro Designer v9.0 was used to evaluate the feasibility of this approach. This design is on par with the current market, by exceeding an annual production rate of 10 kilotons of succinic acid from 50 tons of corn stover per batch. The plant’s economic standing is very attractive with a payback time of under five years and return on investment around 20%. This article shows a facility design that maximizes profitability for a feasible and sustainable solution for bio-based succinic acid production.